2020
DOI: 10.1186/s12889-020-09902-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the uptake of tuberculosis preventative therapy for people living with HIV in Namibia: a multiple methods analysis

Abstract: Background In 2016, Namibia had ~ 230,000 people living with HIV (PLHIV) and 9154 new tuberculosis (TB) cases, including 3410 (38%) co-infected cases. TB preventative therapy (TPT), consisting of intensive case finding and isoniazid preventative therapy, is critical to reducing TB disease and mortality. Methods Between November 2014 and February 2015, data was abstracted from charts of PLHIV enrolled in HIV treatment. Fifty-five facilities were purposively selected based on patient volume, type and location. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…Integration of HIV and TPT care was a facilitator for multiple steps in 7 studies [ 18 , 38 , 72 , 74 , 76 , 79 , 82 ]. Barriers were reported by 12 studies [ 18 , 21 , 24 , 34 , 58 , 66 , 70 , 72 , 74 , 78 , 80 , 81 ], primarily at the initial steps of identification and testing and the final steps of initiating and completing TPT. Nonintegrated TB and HIV care was a barrier for at multiple steps [ 34 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integration of HIV and TPT care was a facilitator for multiple steps in 7 studies [ 18 , 38 , 72 , 74 , 76 , 79 , 82 ]. Barriers were reported by 12 studies [ 18 , 21 , 24 , 34 , 58 , 66 , 70 , 72 , 74 , 78 , 80 , 81 ], primarily at the initial steps of identification and testing and the final steps of initiating and completing TPT. Nonintegrated TB and HIV care was a barrier for at multiple steps [ 34 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pill burden, fear of adverse events, and stocks out of LTBI drugs were also reported as barriers for starting and completing TPT [18,34,72,74,78]. [18,38,72,74,76,79,82] • Fragmentation of care of HIV and TB patients [34,81] • Testing and TPT were implemented by TB programs that were not familiar with the care of HIV patients [66] • Stigma of HIV patients receiving care in TB clinics [72,74] • Lack of information, motivation, and support to HCW [21,80,81] • Too much workload [81] Identification • Participation of staff in the design of TPT implementations strategy [70] • Patient education material [70] • HIV testing for household contacts of infectious TB disease [38,71] • Community HCWs initiating contact [71] • TB/HIV care in antenatal care services [73,75] • Creation of a TB/HIV integration officer and a TB screening officer [76] • Task shifting TB screening to primary care [76] • None Identified Initial testing • Theoretical training on TST [18,24] • TST training [18,24,70] • Extra consultation room [18] • TB screening by "lay counselor" [18] • TB screening done by physicians [24] • TB nurse dedicated for administration of TST [24] • TB counseling at the moment of HIV diagnosis…”
Section: Plos Medicinementioning
confidence: 99%
“…Access to TPT has improved recently, with 3.5 million PLHIV receiving TPT in 2019 [1]. However, in many settings, less than half of those initiating TPT with the standard 6-month course of daily isoniazid complete treatment [4][5][6]. Safer, shorter TPT regimens are now available, including a 12-dose weekly regimen of isoniazid-rifapentine (3HP) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“… 26 A retrospective study from Namibia evaluating TPT uptake in PLHIV found that only 20% of eligible patients completed the TPT cascade of care. 27 A cross-sectional study from Zambia also found low TPT completion rates with only 38% of the 25% of eligible PLHIV who initiated TPT completing treatment. 28 …”
Section: Challenges That Drive Tb-related Mortality In Plhivmentioning
confidence: 99%
“… 84 Improving the efficiency of healthcare systems and effective training on TPT may also allow for better implementation of TPT and reduced TB mortality in PLHIV. 27 , 28 …”
Section: Potential Solutions To Mitigate Tb-related Mortality In Plhivmentioning
confidence: 99%